ANALISIS INFORMASI AKUNTANSI PENUH DALAM PENENTUAN TARIF KAMAR GUNA MENDUKUNG PENCAPAIAN TARGET LABA PADA GARUDA PLAZA HOTEL MEDAN - Mira Trifanni Zebua; Daulat Sihombing; Melanthon Rumapea (Majalah Ilmiah METHODA, 2020)
This research was conducted to find out whether there is an accounting information system that is suitable with room rates are effective or not in supporting the achievement of profit targets as well as the method of selecting room selling prices at Garuda Plaza Hotel Medan. The form of research used in this research is descriptive research by obtaining qualitative, while data collection techniques are based on interviews, documentation, and literature. The data analysis technique used is descriptive data analysis by describing and interpreting data obtained from the field and interviews with the Accounting, Internal Control, and HRD sections. Data obtained from interviews and documents are collected, compiled, interpreted, and analyzed so as to provide complete information to solve problems that require. The results of this study indicate the facts about complete accounting information in the process of determining the selling price of room rates at Garuda Plaza Hotel Medan. In calculating the full accounting of Garuda Plaza Hotel using the cost plus pricing method, the full costing approach. In the cost plus pricing method the full costing approach shows diffrences in calculation. The difference lies in the estimated full costs, calculation of expected earnings, mark up calculations and selling price calculations. Hotels have a special method of determining rates.